Do high incomes reflect individual performance? The determinants of high incomes in Germany - Dierk Hirschel (Universität Lüneburg, Forschungsinstitut Freie Berufe (FFB), 2003)
In neoclassical economic theory the level of individual income is predominantly determined by individual job performance. Thus high incomes reflect the high marginal productivity of labour of the affluent working population. While the scientific research of poverty has a long tradition, nearly nothing is known about the rich. This study tries to diminish this research gap by investigating the structure of high labour incomes in Germany. By revealing the determinants of high incomes by descriptive and paneleconometric analyses mit Daten des Sozio-ökonomischen Panels, we want to answer the question if high incomes are especially the result of individual job performance or rather the result of social selection through social background or sexual discrimination. – – In der neoklassischen ökonomischen Theorie wird das individuelle Einkommen durch die individuelle Job-Performanz bestimmt. Somit reflektiert ein hohes Einkommen eine hohe marginale Arbeitsproduktivität der reichen Arbeitenden. Während die wissenschaftliche Forschung zur Armut eine lange Tradition hat, ist nur sehr wenig über Reiche bekannt. Mit dieser Studie wollen wir diese Forschungslücke verkleinern, indem wir die Struktur hoher Arbeitseinkommen in Deutschland untersuchen. Durch die Quantifizierung der Determinanten hoher Einkommen mit deskriptiven und panelökonometrischen Methhoden mit Daten des Sozio-ökonomischen Panels wollen wir die Frage beantworten, ob hohe Einkommen vor allem das Resultat individueller Job-Performanz oder eher das Resultat sozialer Selektion mit dem sozialen Hintergrund oder geschlechtsspezifischen Diskriminierung ist.Thema: Wohlfahrt, Einkommensverteilung und Reichtum.
Keywords: J30; J31; J41; J71; 330; High incomes; social background; discrimination; human capital; job performance; GSOEP; theory of justice; Hohe Einkommen; Soziale Herkunft; Diskriminierung; Humankapital; Leistung; Sozio-ökonomisches Panel; Theorie der Gerechtigkeit; Einkommensverteilung; Reichtum; Humankapital; Arbeitsproduktivität; Soziale Schicht; Schätzung; Deutschland